Eksplorasi Penggunaan Media Interaktif Berbasis IT dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Negeri 1 Lepak - Samsul Hadi Hidayatullah; Jaelani, Abdul Kadir (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to examine in depth the implementation of information technology (IT)-based interactive media in the learning process at the elementary school level and to identify its influence on enhancing students’ learning interest. The research was conducted at SDN 1 Lepak, located in East Sakra Subdistrict, Central Lombok Regency. This study employed a qualitative approach with an exploratory method. Data collection techniques included direct classroom observations, in-depth interviews with key informants, and the collection of supporting documents. The research informants consisted of the school principal, classroom teachers, and upper-grade students. The collected data were analyzed using the interactive model developed by Miles and Huberman, which comprises three main stages: data reduction, data display, and systematic conclusion drawing. The findings indicate that teachers at SDN 1 Lepak have actively utilized various forms of interactive learning media, including educational videos, digital images, technology-based quizzes, and other digital learning applications. The use of these media has been proven to encourage active student participation and strengthen their understanding of the learning materials. From the students’ perspective, the use of interactive media has had a positive impact on learning motivation, as reflected in increased enthusiasm, active engagement, and conceptual understanding. Challenges such as technical limitations and initial student adaptation were effectively addressed through teacher guidance and internal school training. Overall, the results demonstrate that IT-based interactive media are effective in promoting active participation, creating an enjoyable learning environment, and enhancing students’ comprehension, in line with the principles of cognitivism and constructivism, and are therefore recommended for implementation in elementary schools.